Minimalizing Non-point Source Pollution Using a Cooperative Ion-Selective Electrode System for Estimating Nitrate Nitrogen in Soil - Su, Rui; Wu, Junfeng; Hu, Jiandong; Ma, Liuzheng; Ahmed, Shakeel; Zhang, Yanyan; Abdulraheem, Mukhtar Iderawumi; Birech, Zephania; Li, Linze; Li, Can; Wei, Wentao (Frontiers in Plant Science, 2022)
Nitrate nitrogen (NO3- -N) in the soil is one of the important nutrients for growing crops. During the period of precipitation or irrigation, an excessive NO3- -N readily causes its leaching or runoff from the soil surface to rivers due to inaccurate fertilization and water management, leading to non-point source pollution. In general, the measurement of the NO3--N relies upon the laboratory-based absorbance, which is often time-consuming, therefore not suitable for the rapid measurements in the field directly. Ion-selective electrodes (ISEs) support the possibility of NO3--N measurement by measuring the nitrate (NO3-) ions in soil quickly and accurately due to the high water solubility and mobility of NO3- ions. However, such a method suffers from a complicated calibration to remove the influences caused by both temperature and other ions in the measured solution, thus limiting field use. In this study, a kind of all-solid ISE system combined with a temperature sensor and a pH electrode is proposed to automatically measure the concentrations of the NO3--N. In this study, a soil water content calibration function was established, which significantly reduces a relative error (RE) by 13.09%. The experimental results showed that the stabilization time of this electrode system was less than 15 s with a slope of −51.63 mV/decade in the linear range of 10–5–10–2.2 mol/L. Both the limit of detection of 0.5 ppm of the NO3--N and a relative SD of less than 3% were obtained together with the recovery rate of 90–110%. Compared with the UV-Vis spectroscopy method, a correlation coefficient (R2) of 0.9952 was obtained. The performances of this all-solid ISE system are satisfied for measuring the NO3--N in the field.